Faktor- Faktor yang Memengaruhi Return Saham Pada Perusahaan Mining yang Terdaftar di Bursa Efek Indonesia Periode 2011-2020 - Oktaviani, Erika; Beny, Beny (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study was to determine the effect of return on equity, debt-to-equity ratio, total asset turnover, earnings per share, price book to value, market value added, economic value added, and net profit margin on stock returns in the mining sector companies that listed on the Indonesia Stock Exchange for the 2011- 2020 period. The object used in this study is the Mining sector companies listed on the Indonesia Stock Exchange. This study used a sample of 13 companies using the Purposive Samplings data collection technique. Methods of data analysis using multiple regression analysis with panel data approach. The results of this study, return on equity, debt-to-equity ratio, total asset turnover, earnings per share, market value added, economic value added, and net profit margin does not affect stock returns. Meanwhile, price book to value and market value added affect stock returns.